Power Generation Investment Timing in a Post Covid-Era - Csapi, Vivien; Posza, Alexandra (International Journal of Energy Economics and Policy, 2021)
This paper deals with the optimal timing of power generation investments in the second year of the global COVID-19 pandemic. The research applies the real options methodology during the investment decision-making process and takes, besides a proper uncertainty assessment, the project embedded flexibilities into account. Timing flexibility is discussed thoroughly, and the issue of optimal exercise, the timing of the highest potential value creation is examined through a static and dynamic lens. The authors’ initial hypothesis presumed uncertainty as the most influential parameter measured by the project’s standard deviation. Timing flexibility, optimal timing is analyzed compared to and concerning this volatility. Static and real options-based dynamic investment timing models are being tested in the power generation industry. Of particular interest of the research is whether results could prove the phenomena of renewable technologies being the safe haven of energy investments after the sector became highly volatile due to the COVID-19 pandemic. Results show that the timing of real options and the value will have a positive relationship. Still, the most exciting finding is that time and timing have a more substantial effect on the created value than uncertainty and further embedded growth potential (more flexibility). Keywords: real options, timing, flexibility, power generation, uncertainty JEL Classifications: G11, C41 DOI: https://doi.org/10.32479/ijeep.11815